Determination of a setup correction function to obtain adsorption kinetic data at stagnation point flow conditions - Mora, Maria F. (2010)
This paper is the first report on the characterization of the hydrodynamic conditions in a flow cell designed to study adsorption processes by spectroscopic ellipsometry. The resulting cell enables combining the advantages of in situ spectroscopic ellipsometry with stagnation point flow conditions. An additional advantage is that the proposed cell features a fixed position of the " inlet tube" with respect to the substrate, thus facilitating the alignment of multiple substrates. Theoretical calculations were performed by computational fluid dynamics and compared with experimental data (adsorption kinetics) obtained for the adsorption of polyethylene glycol to silica under a variety of experimental conditions. Additionally, a simple methodology to correct experimental data for errors associated with the size of the measured spot and for variations of mass transfer in the vicinity of the stagnation point is herein introduced. The proposed correction method would allow researchers to reasonably estimate the adsorption kinetics at the stagnation point and quantitatively compare their results, even when using different experimental setups. The applicability of the proposed correction function was verified by evaluating the kinetics of protein adsorption under different experimental conditions. © 2010.